Functionally Modified Polyolefin-Based Separators for Lithium-Sulfur Batteries: Progress and Prospects - Li, Jiaojiao; Xiao, Zhen; Chen, Anqi; Zhang, Wenkui; Zhu, Dongmin; Jin, Yanxian; Mao, Qinzhong; Wang, Guoguang; He, Jiarui; Xia, Yang (Frontiers in Energy Research, 2020)
The ever-growing demands of portable devices and electric vehicles are drawing widespread attention to advanced energy storage systems. Over the past decades, lithium-sulfur batteries (LSBs) are of vast potential to act as the next-generation rechargeable power source due to its high theoretical specific energy, cost-effectiveness, and environmental benignity. However, the insufficient sulfur utilization, inferior cyclability, and rate capability originating from the intrinsic insulating feature of sulfur and notorious polysulfide shuttle are the major obstacles to fulfilling the industrialization of LSBs. In this respect, the introduction of functional barrier layer coating on separator has been verified as an effective strategy to overcome the aforementioned intractable problems. In this review, we focus on summarizing the current progress of the modified polyolefin-based separators (called as functional separators), including functional separators facing cathode (FSFC) and functional separators facing anode (FSFA). According to the working mechanism, FSFCs are divided into physical adsorption separators, chemical adsorption separators, catalytic conversion separators, and multifunctional separators. Meanwhile, FSFAs are classified into physical barrier separators, induced lithium growth separators, regulated lithium nucleation separators, and hybrid mechanisms separators, respectively. Finally, the future perspective coupled with the practical utilization of functional separators in LSBs is proposed.